Gut microbiota regulates serum metabolites in mice with nonalcoholic fatty liver disease via gut metabolites: mechanisms involving branched-chain amino acids and unsaturated fatty acids - Qiu, Hao; Wen, Yuhang; Luo, Yadan; Lv, Shuya; Huang, Jingrong; Chen, Baoting; Lu, Ruilin; He, Lvqin; Yang, Qian; Han, Jianhong; Yan, Xuefeng; He, Manli; et al. (Frontiers in Endocrinology, 2025)
IntroductionIn recent years, nonalcoholic fatty liver disease (NAFLD) has become the most common chronic liver disease globally. Studies indicate that the gut-liver axis plays an important role in the occurrence and development of this disease. Our previous studies showed that the gut microbiota and gut metabolites in mice with NAFLD changed significantly. However, it is unclear whether these changes influenced the disease process through serum metabolites.MethodsWe conducted a non-targeted metabolome analysis on serum metabolites and systematically investigated the correlations between serum metabolites, gut microbiota, gut metabolites, and phenotypic index. Additionally, we traced the potential origins of serum metabolites and analyzed host-microbial interactions to elucidate the underlying mechanisms linking changes in serum metabolites with gut microbiota and gut metabolites.ResultsThe findings suggest that the imbalance of gut pathogenic microbiota, specifically Blautia and Helicobacter, and beneficial microbiota such as Allobaculum, in mice with nonalcoholic fatty liver disease may be an important cause of gut metabolic disorders. This disorder results in a reduction of unsaturated fatty acid content, particularly a decrease in Eicosapentaenoic Acid (EPA) and Docosahexaenoic Acid (DHA), and an accumulation of branched fatty acids in the serum. Consequently, there is a significant elevation in liver injury indices, potentially exacerbating the progression of nonalcoholic fatty liver disease and obesity in mice.DiscussionThese results suggest that serum metabolites are influenced by gut microbiota and their metabolites. The variations in serum metabolites provide valuable insights into the relationship between gut microbiota and their metabolites in the context of nonalcoholic fatty liver disease.